iStent Trabecular Micro-Bypass Stent Implantation with Cataract Surgery in a Japanese Glaucoma Population - Nitta K (Dove Medical Press, 2020)
Koji Nitta,1 Yutaro Yamada,1 Satomi Morokado,1 Kazuhisa Sugiyama2 1Department of Ophthalmology, Fukui-Ken Saiseikai Hospital, Fukui, Fukui Prefecture, Japan; 2Department of Ophthalmology, Kanazawa University, Kanazawa, Ishikawa Prefecture, JapanCorrespondence: Koji NittaFukui-Ken Saiseikai Hospital, Funabashi 7-1, Wadanaka-Cho, Fukui City, Fukui 918-8503, JapanTel +81 776 23 1111Email nitta.koji7001@fukui.saiseikai.or.jpIntroduction: This study assesses two-year efficacy and safety following implantation of a single trabecular micro-bypass stent (iStent®) with concomitant phacoemulsification cataract surgery in Japanese patients with open-angle glaucoma (OAG).Materials and Methods: This retrospective, consecutive case series included eyes that underwent iStent implantation with phacoemulsification and were followed for 24 months postoperative. Efficacy and safety measures included intraocular pressure (IOP), number of glaucoma medications, adverse events, secondary surgeries, visual fields, and endothelial cell counts.Results: Of 73 operated eyes, 53 eyes had 24 months of follow-up and are analyzed. Diagnoses included primary open-angle glaucoma (POAG, n=25), normal-tension glaucoma (NTG, n=16), and pseudoexfoliative glaucoma (PXG, n=12). At 24 months, mean IOP reduced by 18% to 13.6± 3.0 mmHg versus 16.5± 3.4 mmHg preoperatively (p< 0.0001), and mean medication number reduced by 81% to 0.37± 0.74 versus 1.96± 0.98 preoperatively (p< 0.0001). The percentage of medication-free eyes was 77% versus 0% preoperatively, and 81% of eyes had IOP ≤ 15 mmHg versus 42% preoperatively. Results were similarly favorable across glaucoma subtypes (POAG, NTG, PXG). Notably, mean IOP in NTG eyes decreased to 12.8± 1.4 mmHg from 14.4± 3.0 mmHg preoperatively (p=0.03), and medications decreased by 87% to 0.31± 0.70 versus 2.38± 0.72 preoperatively (p< 0.0001). At 24 months, 81% of NTG eyes were medication-free (versus 0% preoperatively); 2 NTG eyes (13%) were on ≥ 2 medications (versus 100% preoperatively). Throughout the follow-up, visual fields and endothelial cell counts remained stable; 1 eye (1.9%) underwent filtration surgery.Discussion: Favorable safety and significant IOP and mediation reductions were achieved through two years following iStent implantation with phacoemulsification in a Japanese population. These gains were achieved across all glaucoma subtypes (including POAG, NTG, PXG).Conclusion: This real-world study supports the viability of iStent implantation to treat Japanese patients with glaucoma and shows that the benefits extend to those with NTG or PXG in addition to POAG.Keywords: microinvasive glaucoma surgery, MIGS, iStent, trabecular micro-bypass, Japanese, normal-tension glaucoma